2008
DOI: 10.1089/ast.2006.0102
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Identification in Natural Jarosites Using Laser Desorption Fourier Transform Mass Spectrometry: Implications for the Search for Life on Mars

Abstract: The jarosite group minerals have received increasing attention since the discovery of jarosite on the martian surface by the Mars Exploration Rover Opportunity. Given that jarosite can incorporate foreign ions within its structure, we have investigated the use of jarosite as an indicator of aqueous and biological processes on Earth and Mars. The use of laser desorption Fourier transform mass spectrometry has revealed the presence of organic matter in several jarosite samples from various locations worldwide. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(78 citation statements)
references
References 34 publications
7
71
0
Order By: Relevance
“…In 2004, jarosite was detected by the Mars Exploration Rover (MER) M6ssbauer spectrometer (KlingelhOfer et al 2004), which has been interpreted as strong evidence for the occurrence of large amounts of water (and possibly life) in the history of Mars. A recent study using laser desorption Fourier transfonn mass spectrometry revealed the presence of organic matters (such as glycine) in several jarosite samples (Kotler et al 2008), thereby validating the hypothesis of possible existence of life on Mars.…”
Section: Introductionmentioning
confidence: 69%
“…In 2004, jarosite was detected by the Mars Exploration Rover (MER) M6ssbauer spectrometer (KlingelhOfer et al 2004), which has been interpreted as strong evidence for the occurrence of large amounts of water (and possibly life) in the history of Mars. A recent study using laser desorption Fourier transfonn mass spectrometry revealed the presence of organic matters (such as glycine) in several jarosite samples (Kotler et al 2008), thereby validating the hypothesis of possible existence of life on Mars.…”
Section: Introductionmentioning
confidence: 69%
“…The minerals impact detection; desorption and ionization of the biomarker is dependent on the energy of the laser absorbed by the mineral matrix and converted to heat. Evaporates like halite and jarosite yielded a signal, but hematite did not (Yan et al, 2007;Kotler et al, 2008;Richardson et al, 2008). Amino acids incorporated within halite yielded a better signalto-noise ratio than those applied to its surface (Yan et al, 2007).…”
Section: Impact Of Mineralogy On the Extraction Of Biomarkersmentioning
confidence: 95%
“…However, a systematic evaluation of LDI efficiency in extracting biomarkers appears to be lacking. A few studies have addressed how minerals may act as a geological matrix that aids desorption and ionization of amino acids, fatty acids, and small proteins by a laser, comparable to matrixassisted laser desorption/ionization (MALDI) (Yan et al, 2007;Kotler et al, 2008;Richardson et al, 2008). The minerals impact detection; desorption and ionization of the biomarker is dependent on the energy of the laser absorbed by the mineral matrix and converted to heat.…”
Section: Impact Of Mineralogy On the Extraction Of Biomarkersmentioning
confidence: 99%
“…The Urey instrument, an advanced in situ organic and oxidant detector, originally proposed for the Exomars mission, developed a sub-critical water extraction system to separate and concentrate the organic compounds from the mineral matrix (Aubrey et al 2008). Due to the potential difficulty of extracting organic matter from mineral matrices because of adsorption and/or potential substitution within the mineral structure (Kotler et al 2009), direct laser desorption and ionization techniques (such as those being explored for the Exomars mission) and related techniques for sample return missions (Yan et al 2007;Kotler et al 2008;Richardson et al 2008) may provide the needed methods to release and detect potential biosignatures.…”
Section: Eurogeomars 2009 Campaign: Astrobiology and Habitability Stumentioning
confidence: 99%